Global media ethics : problems and perspectives - Ward, Stephen J. A. (Stephen John Anthony), 1951- (Chichester, West Sussex, UK : Wiley-Blackwell, 2013)
'Global Media Ethics is the first comprehensive cross-cultural exploration of the conceptual and practical issues facing media ethics in a global world. A team of leading journalism experts investigate the impact of major global trends on responsible journalism. The first full-length, truly global textbook on media ethics; Explores how current global changes in media promote and inhibit responsible journalism; Includes relevant and timely ethical discussions based on major trends in journalism and global media; Questions existing frameworks in media ethics in light of the impact of global media; Contributors are leading experts in global journalism and communication '--
Includes bibliographical references and index.
Keywords: Journalistic ethics; Mass media -- Moral and ethical aspects